Multimedia Development for Learning Materials for Jepin Gresik Pantai Dance for Junior High School Students - Agisna Niswatana; Aunurrahman; Usman Radiana; Indri Astuti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This study uses the ADDIE Robert Maribe Branch paradigm. This research develops Flash CS multimedia. Followed by 42 students of SMP N 18 North Pontianak even semester 2021/2022. Pre-study to the stage, students participate. Pre and post tests, interviews, validation questionnaires, observations, and documentation were used in this study. Qualitative and quantitative data. The average assessment of media experts is 4.45 with 89% in the "Very Valid" category, while the assessment of learning media design is 4.5 with 90%. "Applicable" category. the average expert rating is 3.47 with 87.4% in the very decent category. The teacher's reaction to the product trial averaged 4.51 with 90.2% in the very appropriate category, while the student trial on the individual trial averaged 4.32 with 86.4 percent in the accepted criteria. The small group experiment averaged 4.71 with 9.42% strongly agree. The large-scale test averaged 4.62 with 9.24% strongly agree. The GAIN N-efficacy test reached 0.64, "very effective." Interesting learning videos.